The role of atypical PKC iota in glioblastoma multiforme - Garratt-Lalonde, Michelle (University of Ottawa (Canada), 2003)
Glioblastoma multiforme, a high grade malignant astrocytoma, is the most common and mortal intracranial tumor in adults. The median survival time for glioblastoma patients remains from 9--12 months despite aggressive treatment programs. These high-grade central nervous system tumors bear genetic and molecular aberrations that result in innate chemoresistance to commonly used chemotherapeutic agents. The main focus of this thesis is on exploring signaling events downstream of phosphoinositide 3-kinase (PI3-K) in glioblastoma multiforme in attempts to discover molecular targets that may be highly specific and thus less toxic therapeutic targets. The PI3-K pathway is constitutively activated in glioblastoma. The Protein Kinase C family of serine/threonine kinases is activated downstream of PI3-K. Our focus is placed on a member of the atypical protein kinase C subfamily called, atypical PKC iota. We finally began examining the role of atypical PKC iota and invasion in U87MG glioblastoma cells using scratch/wound assays. (Abstract shortened by UMI.)
Keywords: Health Sciences, Oncology.